CHARACTERIZATION OF GLUTATHIONE-S-TRANSFERASES-SUPPRESSION OF ANTIOXIDANT ENZYMES BY ACRYLAMIDE IN DEVELOPING CHICK EMBRYONIC BRAIN - M. VENKATASWAMY,; K. DIVYA,; C. PALLAVI,; K. THYAGA RAJU, (International Journal of Pharma and Bio Sciences, 2013)
Glutathione-S-transferases (GSTs) constitute a multifunctional family of dimeric and cytosolic enzymes which play an important role in biotransformation of tissues from oxidative stress. They catalyze the conjugation of intracellular glutathione with chemicals, that possess an electrophilic centre to facilitate their metabolism and elimination through mercapturic acid pathway. Acrylamide, a known neurotoxicant, causes damage to almost all organs including brain, liver, testis, and kidney. In the present study, effect of acrylamide was evaluated on GST activities, total-specific activity using substrates and purified from 11th old day developing chick embryonic brain tissue by a glutathione affinity matrix chromatography column, and the GST protein pattern was investigated on sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). The results on activities of glutathione-S-transferases (GSTs) have been shown an increase up to 0.4mg of acrylamide and decline from 0.5 to 0.6mg of acrylamide due to dose dependant acrylamide treatment. The GSTs were purified to 37.36-fold with an yield of 62%, with a specific activity of 25.18 U/mg protein from chick embryonic brain using glutathionyl linked Agarose affinity chromatography. The SDS-PAGE analysis of chick embryonic brain purified GSTs were resolved in to three bands, CB1 (α), CB2 (µ) and CB3 (π), with relative molecular weights of 29.0, 26.0 and 24.0 kDa, respectively. The present data conclude that acrylamide as neurotoxicant induces oxidative stress in developing chick embryo brain due to suppression of the antioxidant enzymes. Further GST proteins were purified to electrophoretic homogeneity with an overall yield of 37.36% showed α, µ and π class GSTs protein bands.